PENGARUH TEKNOLOGI INFORMASI, PENGENDALIAN INTERN, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA INSTANSI PEMERINTAH (Studi Empiris Pada SKPD Kabupaten Bengkalis) - Lestari, Tri Putri; -, Kennedy; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this sstudy is technology information, internal control and leadership style of the performance of government agencies at SKPDs Bengkalis Regency. The research method used is descriptive research method with survey approach, the type of data used iss primary data, primary data by sending questionnaires directly to the respondents and take it back after a predetermined time period. The study population is SKPDs Bengkalis Regency. The sample was echelons III and IV on bodies and agencies in Bengkalis Regency. The classical assumption used is the test for normality, multicollinearity test and test heterokedastisitas. Hypothesis testing using Adjusted R square, Model analysis of the data used I multiple linear regression. Testing the quality of the data used are validity and reliability testing. Simultaneouss significant (Test-f), partial significance (Test-t), the hypothesis testing results show that the hypothesis first, second and third received, this suggests that information technology, internal control and leadership style of the performance of government agencies at SKPDs Bengkalis Regency.Keywords: Information Tecnhology, Internal Control,Leadership style and performance of government agencies.